PELAKSANAAN FUNGSI DPRD KABUPATEN KARANGANYAR - Budi Santosa (JI@P, 2022)
This study aims to analyze and describe the implementation of the NgawiRegent's regulation policy number 14 of 2019 regarding the instructions forimplementing regional regulations regarding smoke-free areas in the KarangjatiDistrict, Ngawi Regency. This type of research is descriptive qualitative. Datacollection was carried out through interviews with the person in charge of the KTRsuch as the sub-district head, the head of the health center, the village head andreinforced by the responses of community leaders in the Karangjati sub-district,Ngawi district. Data analysis using Miles and Huberman Model. Implementationof the research refers to the theory of Van Metter and Van Horn. The results of thestudy found that the implementation of the policy has not run optimally, asevidenced by the occurrence of violations, there are no special employees whoregulate the implementation of the KTR policy and the funds to implement the KTRpolicy are still limited, the implementing agent has not obtained the Regent'sDecree, public awareness of the dangers of smoking and orderly implementation ofthe policy. KTR is low, coordination between agencies is not optimal because itfocuses on its own work area, and environmental conditions around KTR do notsupport the implementation of KTR policies. Suggestions that can be submitted are(1) it is necessary to appoint an implementing officer for controlling KTR policiesto be strengthened through a Regent's Decree; (2) Provision of special funds tocreate various kinds of socialization media about KTR. Keywords: size and policy objectives, resources, characteristics; attitude orinclination, communication